Ответы и объяснения

2014-01-03T09:13:06+00:00
Пусть  \frac{1}{cos^{2}x}=y , тогда
cos^{2} x= \frac{1}{y}
sin^{2}x=1- \frac{1}{y} = \frac{y-1}{y}
 \frac{1}{sin^{2}x}= \frac{y}{y-1}

Уравнение примет вид:
y- \frac{4y}{y-1} +6=0
 \left \{ {{y(y-1)- 4y +6(y-1)=0} \atop {y \neq 1}} \right.

y^{2}-y-4y+6y-6=0
y^{2}+y-6=0
y_{1}=-3
y_{2}=2

cos^{2}x= \frac{1}{-3} - не имеет корней

cos^{2}x= \frac{1}{2}
 \frac{1+cos2x}{2}= \frac{1}{2}
1+cos2x= 1
cos2x=0
2x= \frac{ \pi }{2} + \pi n, n \in Z
x= \frac{ \pi }{4} +  \frac{ \pi n}{2} , n \in Z